Avaliação do status nutricional de iodo em gestantes atendidas no pré-natal do Hospital das Clínicas da Universidade Federal de Minas Gerais - Natália Campos Gonçalves Scherr (2019)
During pregnancy, there is an increased of thyroid hormone, a significant increased iodine renal clearance and increased thyroxine (T4) turnover by placental type 3 deiodinase in the second half of pregnancy, thus leading to increased iodine demand. The aim of this study was to evaluate the nutritional status of iodine in pregnant women attending in prenatal care at the hospital of the Universidade Federal de Minas Gerais. We analyzed urinary iodine concentration in 30 pregnant women with single pregnancy and gestational age less than 20 weeks. Casual single urine samples were collected for urinary iodine concentration measurement by inductively coupled plasma detector method. Median urinary iodine concentration of the pregnant women studied was 216.73 mcg/L, which is adequate for the group according to World Health Organization (WHO). This study demonstrates that despite the increased demand for iodine among pregnant women and ANVISA's recommendation to reduce salt iodine levels, the population of pregnant women attended at the Instituto Jenny Faria de Atenção à Saúde do Idoso e da Mulher of the Universidade Federal de Minas Gerais is considered sufficient in iodine. Although a larger sample is needed to consolidate these findings, we believe it is early to recommend universal iodine supplementation for Brazilian pregnant women and more studies are necessary to a conclusion. Iodine supplementation for pregnant women in accessible iodine areas is associated with risk of excessive iodine exposure to the fetus.